Internal flow structures in columnar jointed basalt from Hrepphlar, Iceland II: Magnetic anisotropy and rock magnetic properties - Almqvist, Bjarne S.G.; Bosshard, Sonja A.; Hirt, Ann Marie; id_orcid:0 000-0002-2193-0472; Mattsson, Hannes B.; Hetényi, György (Springer, 2012)
ISSN:0258-8900 ISSN:1432-0819